2021
DOI: 10.3390/mi12020156
|View full text |Cite
|
Sign up to set email alerts
|

Simulative and Experimental Characterization of an Adaptive Astigmatic Membrane Mirror

Abstract: Adaptive optical (AO) components play an important role in numerous optical applications, from astronomical telescopes to microscope imaging systems. For most of these AO components, the induced wavefront correction, respectively added optical power, is based on a rotationally symmetric or segmented design of the AO component. In this work, we report on the design, fabrication, and characterization of a micro-electronic-mechanical system (MEMS) adaptive membrane mirror in the shape of a parabolic cylinder. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…(e) An electrothermal bimorph-actuated MOEMS mirror [41] . (f) A 3D curved micromirror for collimating the output beam of single-mode fibers [42] . (g) Cross section and top view of an electromechanically driven adaptive astigmatic membrane mirror [43] .…”
Section: Micromirrors and Micromirror Arraysmentioning
confidence: 99%
See 4 more Smart Citations
“…(e) An electrothermal bimorph-actuated MOEMS mirror [41] . (f) A 3D curved micromirror for collimating the output beam of single-mode fibers [42] . (g) Cross section and top view of an electromechanically driven adaptive astigmatic membrane mirror [43] .…”
Section: Micromirrors and Micromirror Arraysmentioning
confidence: 99%
“…The in-plane optical beam collimation is an important performance factor in optical MEMS. It is usually achieved by integrating microlenses in the system [42] , which greatly limits the working wavelength range of the system and increases the manufacturing and assembly cost. In 2017, Sabry et al demonstrated optical fiber light collimation using a Si MEMS 3D curved mirror, as shown in Fig.…”
Section: Micromirrors and Micromirror Arraysmentioning
confidence: 99%
See 3 more Smart Citations